How is an Electronic Screening and Brief Intervention Tool on Alcohol Use Received in a Student Population? A Qualitative and Quantitative Evaluation - Fraeyman, Jessica; Van Royen, Paul; Vriesacker, Bart; De Mey, Leen; Van Hal, Guido (JMIR Publications, 2012)
BackgroundA previous study among Antwerp college and university students showed that more male (10.2%-11.1%) than female (1.8%-6.2%) students are at risk for problematic alcohol use. The current literature shows promising results in terms of feasibility and effectiveness for the use of brief electronic interventions to address this health problem in college and university students. We evaluated this type of intervention and cite existing literature on the topic. ObjectiveTo develop a website, www.eentjeteveel.be, to motivate college and university students with problematic alcohol use to reduce alcohol consumption and increase their willingness to seek help. MethodThe website contained a questionnaire (Alcohol Use Disorders Identification Test [AUDIT]) for students to test their alcohol use. According to their answers, the students immediately received personalized feedback (personal AUDIT score and additional information on risks associated with alcohol use) and a suggestion for further action. Afterward, students could send an email to a student counselor for questions, guidance, or advice. To obtain in-depth qualitative information on the opinions and experiences of students, we held 5 focus group discussions. The topics were publicity, experiences, impressions, and effects of the website. We analyzed the quantitative results of the online test in SPSS 15.0. ResultsMore than 3500 students visited www.eentjeteveel.be; over half were men (55.0%). A total of 34 students participated in the focus group discussions. The mixture of quantitative and qualitative methods to evaluate the intervention allowed a thorough analysis and provided complementary results. The intervention was well received by the student population. However, some minor aspects should be reconsidered, such as website publicity and providing students with options that were added after intermediate evaluation. The intervention increased the motivation of students to think about their alcohol use but could not stimulate them to change their behavior. The website attracted relatively more male than female students and more students in the high-risk group than in the low-risk group. The high-risk group was more inclined to seek advice or guidance (23/400, 6%; χ22 = 32.4, P < .001) than the low-risk group (34/1714, 2%; χ22 = 32.4, P < .001). ConclusionsWe gained unique insight into students' experiences, opinions, and perceptions with regard to the intervention. The results show that the intervention was positively received in the population, and the willingness to seek help was increased. However, real behavior change needs further research. The results of this study can assist health providers and researchers in better understanding college and university students' perceptions of eHealth initiatives.